Solar-stellar astrophysics and dark matter - Turck-Chièze, S. (2012)
In this review, we recall how stars contribute to the search for dark matter and the specific role of the Sun. We describe a more complete picture of the solar interior that emerges from neutrino detections, gravity and acoustic mode measurements of the Solar and Heliospheric Observatory (SOHO) satellite, becoming a reference for the most common stars in the Universe. The Sun is a unique star in that we can observe directly the effect of dark matter. The absence of a signature related to Weakly Interacting Massive Particles (WIMPs) in its core disfavors a WIMP mass range below 12GeV. We give arguments to continue this search on the Sun and other promising cases. We also examine another dark matter candidate, the sterile neutrino, and infer the limitations of the classical structural equations. Open questions on the young Sun, when planets formed, and on its present internal dynamics are finally discussed. Future directions are proposed for the next decade: a better description of the solar core, a generalization to stars coming from seismic missions and a better understanding of the dynamics of our galaxy which are all crucial keys for understanding dark matter.